Peningkatan Hasil Belajar KD Sistem Gerak Manusia melalui Pendekatan Contextual Teaching and Learning - Wahyuningsih (Universitas Pancasakti Tegal, 2017)
The purpose of this study is to improve the learning outcomes of Biology students of class VIII SMP Negeri 3 Comal Pemalang as well as obtaining a biology learning approach appropriate for the basic competence of the human motion system. This study is a Classroom Action Research conducted in 2 cycles. Each cycle includes Planning, Acting, Observing, and reflecting. The test results showed an average increase of 72.9 in cycle I to 84.2 in cycle II. Results Questionnaire respondents showed that in cycle I 65% of students interested in contextual learning and 35% of students are not interested, while in cycle II there are 87.50% of students who are interested in contextual learning and 12.50% of students are not interested in contextual learning. Based on the research results can be concluded that learning CTL on the subject of the human motion system can improve student learning outcomes of grade VII SMP Negeri 3 Comal Pemalang and shows that contextual learning can improve student performance.